Prohibition of Illegal Parking at Novaliches Proper Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Illegal parking is a significant problem in urban areas, as it causes congestion, obstructs trafficflow, and poses safety hazards for pedestrians and motorists. In response, the localgovernment of Novaliches Proper, Quezon City, implemented a prohibition of illegal parking inthe area. This study aimed to evaluate the effectiveness of the prohibition as perceived by 30respondents.The results showed that the majority of the respondents were aware of the prohibition of illegalparking in Novaliches Proper. Of these, they reported that they had observed a positive impacton traffic flow while noting improvements in pedestrian safety. However, some respondentsstill observed instances of illegal parking, reporting that it still occurred frequently. Moreover,some respondents suggested that stricter enforcement was needed to fully eliminate theproblem of illegal parking. Specifically, the respondents suggested increasing fines andpenalties for violators while recommending more frequent monitoring and enforcement bylocal authorities.The findings of this study indicate that the prohibition of illegal parking in Novaliches Properhas had a positive impact on traffic flow and pedestrian safety, as perceived by the majority ofthe respondents. This suggests that the local government's policies and strategies related toillegal parking have been effective in achieving their intended goals. However, the fact thatsome respondents still observed instances of illegal parking suggests that further efforts areneeded to ensure compliance and enforcement. Specifically, the suggestions made by therespondents for increasing fines and penalties, as well as more frequent monitoring andenforcement, could be useful in enhancing the local government's efforts to address theproblem of illegal parking.
Keywords: Criminology